A taq man multiplex real-time pcr for identification of porcine and canine dna in halal food - Pathaburee, Pojchanad (Universitas Ahmad Dahlan, 2021)
The efficient and timely detection of prohibited animals in Halal food is very important. This study aimed to establish a rapid detection method for porcine and canine DNA in a food product. Porcine and Canine DNA were Contaminated in halal food products using multiplex Real-Time PCR shown positive specificity only in Porcine and Canine meat but shown negative results in chicken, cow, and fish. The results from porcine showed that the lowest level is at 0.001% and 0.1% in raw meat and cooked meat heated at 120 degrees celsius for 15 min, and 0.1% in diluted canine DNA respectively. The method for detection of the contamination of porcine and canine DNA in Halal food products with multiplex real-time PCR technique is suitable and high sensitivity for detecting the DNA of prohibited animals in meat products and raw materials, such as detecting contaminated porcine DNA in sweet jelly and soup cubes.